2010
DOI: 10.1128/jvi.02382-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Immunodeficiency Virus Type 1 Integrase in Uncoating of the Viral Core

Abstract: After membrane fusion with a target cell, the core of human immunodeficiency virus type 1 (HIV-1) enters into the cytoplasm, where uncoating occurs. The cone-shaped core is composed of the viral capsid protein (CA), which disassembles during uncoating. The underlying factors and mechanisms governing uncoating are poorly understood. Several CA mutations can cause changes in core stability and a block at reverse transcription, demonstrating the requirement for optimal core stability during viral replication. HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 70 publications
1
48
1
1
Order By: Relevance
“…ing does not occur randomly in the cytoplasm and is critical for infection; but, the exact timing and location of uncoating has been debated (35)(36)(37)(38). Although biochemical analyses of intracellular HIV initially concluded that capsids were lost immediately postfusion (39,40), EM data revealed intact HIV capsids at or near nuclear pores (33) indicating that capsid uncoating does not necessarily precede viral trafficking to the NE.…”
Section: Stochastic Fluorescence Of Single Flash-labeled Tetracysteinementioning
confidence: 99%
“…ing does not occur randomly in the cytoplasm and is critical for infection; but, the exact timing and location of uncoating has been debated (35)(36)(37)(38). Although biochemical analyses of intracellular HIV initially concluded that capsids were lost immediately postfusion (39,40), EM data revealed intact HIV capsids at or near nuclear pores (33) indicating that capsid uncoating does not necessarily precede viral trafficking to the NE.…”
Section: Stochastic Fluorescence Of Single Flash-labeled Tetracysteinementioning
confidence: 99%
“…IN also influences stages of viral replication other than integration, as is evident from the study of IN mutants. While class I IN mutants with substitutions in the catalytic residues block proviral DNA integration, class II IN mutants are defective for viral assembly, particle production, postentry uncoating, reverse transcription, and/or nuclear import (3,14,21,44,45). The exact mechanism by which IN mutants exert these pleiotropic effects is unknown.…”
mentioning
confidence: 99%
“…demonstrated that mutations in the IN gene, including deletion mutants, influence many other stages of viral replication in addition to integration. This pleiotropic effect of IN is characterized by defects in uncoating, reverse transcription, nuclear import, viral gene expression, virion precursor protein processing, and virion morphology (Shin et al, 1994;Engelman et al, 1995;Masuda et al, 1995;Bukovsky & Gottlinger, 1996;Leavitt et al, 1996;Nakamura et al, 1997;Engelman, 1999;Tsurutani et al, 2000;Lu et al, 2004;Dar et al, 2009;Briones et al, 2010). However, the mechanisms for these pleiotropic effects of the IN gene are still poorly understood.…”
Section: Integration Reactionmentioning
confidence: 99%